(untitled) - Bury, J. B. (London, 1913)
Early history of Greece - "before the invader of Aryan speech entered in and took possession, a white folk spread over the islands of the Aegean and along the coast of Asia Minor. The men of this primeval race gave to many a hill and rock the name which was to abide with it fore ever. This race of people developed a civilisation of active trade which in the third millennium spread its influence far beyond the borders of the Aegean. The Aegean peoples therefore plied a busy trade by sea and their maritime intercourse with the African continent can be traced back to even earlier times. The most notable remains of this civilisation have been found at Troy, in the little island of Amorgos, and in the great island of Crete."
Keywords: Hy Lạp,Greece; Lịch sử,History